An investigation of a measles outbreak in Japan and Taiwan, China, March–May 2018 (Western Pacific Surveillance and Response, 2018)
Objective: To investigate a measles outbreak that spread to Japan and China, Taiwan, China during March–May 2018, exploring the characteristics of the super-spreading event.Methods: A contact investigation of the index case and reconstruction of the epidemiological dynamics of measles transmission were conducted. Employing a mathematical model, the effective reproduction number was estimated for each generation of cases.Results and discussion: A single index case gave rise to a total of 38 secondary cases, 33 in Japan and five in China, Taiwan, China. Subsequent chains of transmission were observed in highly vaccinated populations in both Japan and China, Taiwan, China. The effective reproduction number of the second generation was > 1 for both Japan and China, Taiwan, China. In Japan, the reproduction number was estimated to be